Napló. - Hungary. (Orszbággyülés Képviselöházának naplója)
Includes index (általános mutató)
"Hiteles Kiadás."
Not published, 1920-26, during which period the Parliament was suspended and replaced by the National Assembly.
Ceased publication?
Includes index (általános mutató)
Also issued online.
Keywords: Hungary / Politics and government.